The Application of Next Generation Sequencing to the Understanding of Antibody Repertoires - Mathonet, Pascale; Ullman, Christopher (Frontiers in Immunology, 2013)
In the decade since the human genome sequence was declared complete, the development of next-generation sequencing (NGS) or ‘deep’ sequencing to deliver cost-effective genomic sequencing has influenced advances beyond its primary application and changed the research landscape in many other areas. This review will survey recent applications of NGS which have broadened the understanding of natural antibody repertoires (the “antibodyome”) and how these evolve in response to viral infection. We will also report examples where deep sequencing of binding populations, derived from both natural and synthetic repertoires, have been used to benefit antibody engineering. This knowledge will ultimately lead to the design of more effective biological drugs and vaccines.